Perencanaan Arsitektur Enterprise Togaf pada Penerimaan Siswa Baru: Studi Kasus SD Plus IGM (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
The new student admission process at SD Plus IGM is still carried out manually, which results in data inaccuracies and operational inefficiencies. This study aims to design an integrated enterprise architecture plan using the TOGAF (The Open Group Architecture Framework) methodology to improve the efficiency and effectiveness of the student admission process. The research method applied is a qualitative approach through a case study at SD Plus IGM. The findings show that the implementation of TOGAF can align the business, application, data, and technology architecture domains and identify potential risks during the implementation phase. This study provides recommendations for a well-structured and integrated information system plan to support the digital transformation of the student admission process in elementary school settings.